1998
DOI: 10.1002/(sici)1099-1638(199809/10)14:5<331::aid-qre183>3.3.co;2-c
|View full text |Cite
|
Sign up to set email alerts
|

An investigation of ‘cannot duplicate’ failures

Abstract: Various terms such as 'cannot duplicate (CND)', 're-test OK (RTOK)', 'no fault indicated (NFI)', 'no fault found (NFF)', and 'no trouble found (NTF)', are used to describe the inability to replicate field failures during laboratory assessment. This paper uses CND to refer to all such failures. CND failures can make up more than 85% of all observed field failures in avionics and account for more than 90% of all maintenance costs. These statistics can be attributed to a limited understanding of root cause failur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 11 publications
0
10
0
Order By: Relevance
“…References Fault diagnostics [1,2,3,6,7,8,9,10,11,12,13,14,15,16,17,18,19] System design [1,13,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32] Human factors [1,20,32,33,34,35,36,37] Data management [1,20,37,38,39] 1 [1,26] are review papers on the NFF.…”
Section: Categorymentioning
confidence: 99%
See 1 more Smart Citation
“…References Fault diagnostics [1,2,3,6,7,8,9,10,11,12,13,14,15,16,17,18,19] System design [1,13,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32] Human factors [1,20,32,33,34,35,36,37] Data management [1,20,37,38,39] 1 [1,26] are review papers on the NFF.…”
Section: Categorymentioning
confidence: 99%
“…Williams et. al (1998) [10] claim that NFF failures can make up more than 85% of all observed field failures within avionics components. They also account for more than 90% of all maintenance costs, which can be can be attributed to:…”
Section: Financial Implicationsmentioning
confidence: 99%
“…One of the most prominent problems is called No Fault Found (NFF) problem (related terminologies include "cannot duplicate, " "re-test OK, " "trouble not identified, " and "intermittent malfunctions") [10][11][12], particularly in electronic-rich systems. As the name suggests, it refers to the situation that no failure/fault can be detected/replicated during laboratory tests even when the failure has been reported in the field [13]. NFF issues not only make the prognosis and diagnosis extremely difficult, but also can cause skyrocketing maintenance cost.…”
Section: Introductionmentioning
confidence: 99%
“…NFF issues not only make the prognosis and diagnosis extremely difficult, but also can cause skyrocketing maintenance cost. As reported by Williams et al [13], NFF failures account for more than 85% of all filed failures and 90% of overall maintenance costs in avionics; it is estimated that NFF related activities cost the U.S. Department of Defense 2∼10 billion U.S. dollars per year [14]. Evidently, NFF contributes a lot in operational cost in many different application areas.…”
Section: Introductionmentioning
confidence: 99%
“…5 The high number of NFF events can be attributed to a limited understanding of the root causes and characteristics of failures in complex systems, inappropriate means of diagnosing the condition of the systems, and the inability to duplicate field conditions. 6 Some research reported in the literature has shown the importance of NFF events, not just technically, but also organisationally and behaviourally, and has proposed addressing this issue as an integrated problem. 5,7-9 Granstro¨m 10 has described how the number of NFF events in railway signalling systems can be reduced by updating the maintenance requirements for these systems.…”
Section: Introductionmentioning
confidence: 99%